A Martingale approach to the law of large numbers for weakly interacting stochastic processes - Oelschläger, Karl (The annals of probability, 2007)
It is shown that certain measure-valued stochastic processes describing the time evolution of systems of weakly interacting particles converge in the limit, when the particle number goes to infinity, to a deterministic nonlinear process.